Kobiecość i męskość Polaków. Społeczno-kulturowy wymiar płci jako kategoria analityczna = Femininity and masculinity of Poles: the socio-cultural dimension of gender as an analytic category - Paprzycka, Emilia; Mianowska, Edyta; Izdebski, Zbigniew (1956- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this research was to identify the factors differentiating gender on the one hand and, on the other hand, to check how they differentiate the level of satisfaction with selected areas of public and private life. The following research questions have been asked: what is the gender of Poles, and by which socio-demographic variables is it differentiated, do sex and gender differentiate the level of satisfaction with the selected areas of public and private life?
Keywords: kobiecość; męskość; płeć; płeć psychologiczna; satysfakcja z życia; perspektywa płci w badaniach; femininity; masculinity; gender; psychological gender; life satisfaction; gender perspective in researches